Disfunção sexual masculina: compreensão psicanalítica - Kern, Cristina Adriana Rodrigues (Universidade do Vale do Rio dos Sinos, 2010)
This Master's thesis in clinical psychology focused on the case study of patients who showed sexual impotence. Based on the contributions of psychoanalysis, more specifically, the theories of Bleichmar about the constitution of the psyche and of male sex, a study of exploratory qualitative research was designed. We investigated two case studies of patients with erectile dysfunction based on the reports of sessions of psychotherapy. Data were analyzed using the Case Study in Psychoanalysis. We identified significant aspects of family constellation that led to the conclusion about the importance of the effects of the constitution of the psychic apparatus and male sexual constitution on the manifestations of genital sexuality (adult). And also demonstrated the importance of listening to rearrange, beyond the sex life, the power to life.
Keywords: Sexualidade masculina; Silvia Bleichmar; Psicanálise; Intervenção clínica; Disfunção erétil; Male sexuality; Psychoanalysis; Clinical intervention; Erectile dysfunction; ACCNPQ::Ciências Humanas::Psicologia